RESERVING BROTHERHOOD AND KINDNESS: MEGENGAN TRADITION IN WELCOMING RAMADHAN (International Conference on Social and Islamic Studies, 2021)
This study discussed about Megengan tradition. Megengan tradition is a religious traditionin Javanese culture. This tradition started to grow up in society in a long history. The aim sof this research are to explore and find meaningful messages in this unique tradition. Besides for welcoming Ramadhan, this tradition also for praying for our family member who had died. This tradition makes a unique characteristic in society, how culture and Islam are still conserved in one field although both of them are in different fields. It means that society do not avoid the tradition from their ancestry. The researchers used descriptive qualitative with ethnography design. This research’s aim is to describe moredetail about Megengan tradition in Ngancar, Wonogiri. The result of this research show that Megengan tradition still exist in society to conserve the old tradition.